Government Policy Strategies in Developing Healthy Coffee Shops for Community Nutrition-Based Non-Communicable Disease Prevention - Halimatussakdiah Halimatussakdiah; Abdurrahman Abdurrahman; Ismail Ismail; Sofyan Sufri; Irwana Wahab (Jurnal Kesehatan, 2026)
The increasing prevalence of non-communicable diseases (NCDs), such as diabetes mellitus, hypertension, and stroke, in Indonesia is closely linked to unhealthy dietary habits, particularly excessive sugar intake. High sugar consumption contributes to metabolic disorders and cardiovascular risk. The purpose of this study is to support province and district/city policymakers in their efforts to prevent non-communicable diseases. With samples of representatives from the Health Office, Tourism Office, Islamic Sharia Office, coffee shop owners, and coffee drinkers in Banda Aceh City. A qualitative approach was used, involving focus group discussions (FGDs) and in-depth interviews conducted between August 29 and September 20, 2023. A total of 17 participants, including government officials, coffee shop owners, and coffee drinkers, were selected through convenience sampling. Data were collected using semi-structured guides and analyzed using thematic analysis. The findings indicate that coffee consumption is a common social practice, characterized by frequent daily intake and easy access to coffee shops. However, awareness of the health risks associated with excessive sugar consumption remains limited, and healthier menu options are not widely available. Social and cultural factors strongly influence consumption behavior, while participants also emphasized the need for improved health education. These findings suggest the need for practical strategies, including reducing sugar content in coffee, providing low-sugar alternatives, and strengthening community-based nutrition education through cross-sector collaboration. Such efforts are important to promote healthier consumption patterns and reduce NCD risk in Aceh.